2006
DOI: 10.1007/s11524-005-9005-6
|View full text |Cite
|
Sign up to set email alerts
|

Aging and HIV Infection

Abstract: With the advent of highly active antiretroviral therapy (HAART) in mid-1995, the prognosis for HIV-infected individuals has brightened dramatically. However, the conjunction of potent antiviral therapy and longer life expectancy may engender a variety of health risks that, heretofore, HIV specialists have not had to confront. The long-term effects of HIV infection itself and exposure to antiretroviral agents is unknown. Several aspects of aging, including psychiatric disease, neurocognitive impairment, and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 89 publications
0
34
0
1
Order By: Relevance
“…Furthermore, it is likely that gay men may experience higher rates of substance use-related morbidities as they age (Green & Feinstein, 2012). The extant research also provides evidence indicating that older age and HIV independently increase the risk of neurocognitive impairment, particularly in the areas of attention, processing speed, and executive functioning, as well as memory (Hardy & Vance, 2009;Kohli et al, 2006).…”
Section: Health States Of Aging Gay Menmentioning
confidence: 99%
“…Furthermore, it is likely that gay men may experience higher rates of substance use-related morbidities as they age (Green & Feinstein, 2012). The extant research also provides evidence indicating that older age and HIV independently increase the risk of neurocognitive impairment, particularly in the areas of attention, processing speed, and executive functioning, as well as memory (Hardy & Vance, 2009;Kohli et al, 2006).…”
Section: Health States Of Aging Gay Menmentioning
confidence: 99%
“…[2][3][4] Both HIV and aging are thought to impair cognitive, metabolic, and cardiovascular functioning. 2,5 Research is accumulating to suggest that deterioration of these physiological systems is caused in part by systemic immune activation and a chronic inflammatory state, which may persist even when HIV replication is adequately suppressed. In both HIV infection and aging, systemic immune activation causes impaired regenerative capacity and functioning of T cell populations that may hinder antigen-specific responses but may promote generalized inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…They're my rock, they've got to hold me together. (M9, dogs and cat) Buffer Against Self-Destructive Behaviors, Including Suicide: There is evidence that suicide may be a hidden part of the HIV epidemic (Kalichman et al 2000;Kohli et al 2006;Preau et al 2008), and some participants in the current study indicated that an HIV-diagnosis, or the subsequent associated stressors, could be reason to consider this option. Twelve participants also acknowledged their companion animal's supportive presence as a principal reason for not acting on self-destructive thoughts.…”
Section: Reliable Alliancementioning
confidence: 87%